VOLUME 1, NO 1 (2013) - Chief, Editor In (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2013)
It was less than a year ago when the Koya University Council (KUC) decided to separate its official University Journal (Govarí Zankoy Koye) into two separate publications. A journal treating topics in humanities and social sciences to be produced in hard copies; in Kurdish and Arabic, while a solely electronic journal in English dedicated to abstract and applied sciences. Our group was assigned the task of selecting an appropriate title, assembling an editorial board, and creating an editorial policy on reviews and submissions. The title selected for the latter journal was Aro, Kurdish for “today”. Aro is now borne as a peer-reviewed, open source online scientific publication. It is the fruit of great scholarly effort and editorial endeavor by the members of our academic community and the newly formed editorial board of the Journal. We would like to thank all members for their tireless support. Aro was created with a long-term aspiration of becoming a credible regional and international scientific publication, accessible to all in Kurdistan and beyond, and covering a wide range of scholarly disciplines in sciences. The focus of the journal is to reflect that of the Koya University, namely promoting scientific knowledge and research in Kurdistan. We aspire for Aro to become a channel for exchange of research and scholarship by established and aspirant academics and researchers in Kurdistan and worldwide. The warm response from researchers, academics and professionals made our task of creating an editorial Board a relatively easy one. It is clear that having a dedicated and well organized editorial board for the journal is only one side of the coin. The other is the ability to attract submissions of quality research and scholarly work. We are thankful to all of those who put their trust in Aro and presented their original research work and review articles for publication in the premier issue of the journal. Standards of submissions were flexible for the first issue. However, a robust review process has been put in place to ensure a high quality publication based on international norms and standards. We strongly hope that submission of works and articles, high in quantity and quality, continues, as this is the only guarantee for the survival of Aro as a worthy alternative to costly international publications. We at the Editorial Board hope to publish Aro in a semi-annual format, with the hope of expanding its frequency into a quarterly journal in the future. Your support and feedback are invited and appreciated. Sincerely, Professor Khidir M. Hawrami Executive Publisher Dilan M. Rostam, Shwan K. Rachid, Salah I. Yahya, Sarkawt S. Abdulrahman Executive Editorial Board